Penerapan Aspek Etika Bisnis Islam Pada Plagialisasi Foto Dan Video di Online Shop - Amalia, Rachmi Cahya (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2024)
Photo and video plagiarism on online shop platforms is increasing along with the growth of digital commerce. This practice not only violates copyright, but also violates the principles of business ethics. This article discusses the application of aspects of Islamic business ethics in dealing with photo and video plagiarism in online shops. Using a qualitative approach, this research explores how values ​​such as justice, honesty and responsibility recommended in Islam can be applied to prevent and overcome plagiarism. The research results show that the application of Islamic business ethics can be an effective solution in building trust and integrity in the e-commerce ecosystem. It is hoped that these findings can become a reference for online business actors in developing more ethical and responsible business practices.